PESTLE+ risk analysis model to assess pandemic preparedness of digital ecosystems. Issue 1 (13th September 2021) - Anwar, Memoona J.; Gill, Asif Q.; Fitzgibbon, Anthony D.; Gull, Inam
Abstract: COVID‐19 pandemic has affected every country in many ways. Its substantial economic impacts are causing businesses to fade, pushing many nations into an economic downturn. This exposes organizations worldwide to unique risks which cannot be foreseen with conventional methods of risk analysis. This research is part of a broader action design research project conducted in collaboration with industry partner to answer an important research question: How to extend PESTLE risk analysis model to assess pandemic preparedness? In this context, the health factor is added to extend the traditional PESTLE risk analysis model. Furthermore, the interdependence between PESTLE factors has also been investigated, which has not been discussed before. The contribution of this research is the novel PESTLE+ risk analysis model that will help individuals and businesses to improve their understanding of the health crisis, such as the COVID‐19, adjust accordingly and eventually endure the ongoing crisis, which is driving most businesses into liquidation.